Ex 12.2

Ex 12.2, 1

Ex 12.2, 2

Ex 12.2, 3

Ex 12.2, 4 (i) Important

Ex 12.2, 4 (ii)

Ex 12.2, 4 (iii) Important

Ex 12.2, 4 (iv)

Ex 12.2, 5

Ex 12.2, 6

Ex 12.2, 7 (i) Important

Ex 12.2, 7 (ii)

Ex 12.2, 7 (iii) Important You are here

Ex 12.2, 8

Ex 12.2, 9 (i)

Ex 12.2, 9 (ii) Important

Ex 12.2, 9 (iii)

Ex 12.2, 9 (iv) Important

Ex 12.2, 9 (v)

Ex 12.2, 9 (vi)

Ex 12.2, 10 Important

Ex 12.2, 11 (i)

Ex 12.2, 11 (ii) Important

Ex 12.2, 11 (iii) Important

Ex 12.2, 11 (iv)

Ex 12.2, 11 (v) Important

Ex 12.2, 11 (vi)

Ex 12.2, 11 (vii) Important

Last updated at May 7, 2024 by Teachoo

Ex13.2, 7 For some constants a and b, find the derivative of (iii) (x − a)(x − b) Let f(x) = (x − a)(x − b) Let u = (x – a) & v = (x – b) So, f(x) = 𝑢𝑣 f’(x) = 𝑢𝑣′ f’(x) = 𝑢′𝑣 − 𝑣′𝑢 𝑣2 Finding u’ & v’ u = x – a u’ = 1. x1–1 – 0 = x0 = 1 v = x – b v’ = 1.x1–1 – b = 1.x0 = 1 f’(x) = 𝑢𝑣′ = 𝑢′𝑣 − 𝑣′𝑢 𝑣2 = 1 x − b − (1) x − a x − b2 = 1 x − b − (1) x − a x − b2 = x − b − x + a x − b2 = − b + a x − b2 = a − b x − b2 Hence, f’ (x) = 𝐚 − 𝐛 𝐱 − 𝐛𝟐